Gut microbiota induces high platelet response in patients with ST segment elevation myocardial infarction after ticagrelor treatment - Zhang, Xi; Zhang, Xiaolin; Tong, Fangnian; Cai, Yi; Zhang, Yujie; Song, Haixu; Tian, Xiaoxiang; Yan, Chenghui; Han, Yaling (eLife, 2022)
Background:. Ticagrelor is a first-line drug for the treatment of acute ST elevation myocardial infarction (STEMI). However, approximately 20% STEMI patients taking ticagrelor exhibited a delayed response and the mechanism was still unclear. Methods:. To explore the mechanism of the poor response of ticagrelor in post-percutaneous coronary intervention (PCI) patients, we enrolled 65 high platelet reactivity (HPR) patients and 90 controls (normal platelet reactivity [NPR]). Pharmacokinetic assessment result showed that the plasma concentrations of ticagrelor and its metabolism production, AR-C124910XX, were lower in HPR patients than controls. Further single nucloetide polymorphism (SNP) analysis identified that there is no difference in ATP binding cassette subfamily B member 1 (ABCB1) gene expression between the NPR group and the HPR group. Metagenomic and metabolomic analyses of fecal samples showed that HPR patients had higher microbial richness and diversity. Transplantation of the gut microbiota from HPR donors to microbiota-depleted mice obviously decreased plasma concentration of ticagrelor. Results:. Our findings highlight that gut microbiota dysbiosis may be an important mechanism for the ticagrelor of HPR in patients with STEMI and support that modify gut microbiota is a potential therapeutic option for STEMI. Conclusions:. Our findings highlight that gut microbiota dysbiosis may be an important mechanism for the ticagrelor of HPR in patients with ST elevation myocardial infarction (STEMI) and support that modify gut microbiota is a potential therapeutic option for STEMI Funding:. NSFC 82170297 and 82070300 from the National Natural Science Foundation of China.
Keywords: gut microbiota; ticagrelor; coronary heart disease; high platelet reactivity